P275 Course of COVID-19 in patients with Inflammatory Bowel Diseases treated with biologics: the Israeli experience. (27th May 2021) - Lichtenstein, L; Koslowsky, B; Avni-Biron, I; Ovadia, B; Ben-Bassat, O; Naftali, T; Kopylov, U; Haberman, Y; Banai Eran, H; Eliakim, R; Lahat-Zok, A; Hirsch, A; et al.
Abstract: Background: Biologic treatments are inherently associated with an increased risk of infections, and recipients are intuitively considered at-risk for a more severe course of COVID-19. However, the actual risks are not fully described, neither are the appropriate adjustments needed to mitigate such risks. Methods: Nation-wide registry was set up by Israeli IBD Section, to characterize course of COVID-19 in IBD patients who contacted SARS-CoV-2 infection while on biologics. We prospectively collected demographic and clinical data, and analyzed COVID-19 outcomes with regard to the specific treatments. Results: Between Apr and Oct 2020, 144 patients with an established IBD diagnosis and confirmed COVID-19 were enrolled at 20 IBD referral centers. The majority of patients was under the age of 40 (113, 78%), 9 (6%) were younger than 18, only 4 patients (3%) over the age of 70. 94 patients received biologics, as monotherapy (76, 52.8%), combined with immunomodulators (9, 10%) or concomitant corticosteroids (9, 10%). 37 patients (26%) were reported with moderate and severe COVID-19 course, third of them (13) on biologics. 24 patents (17%) were admitted for hospitalization, the rest managed in home setting (114, 79%) and hotels converted into makeshift healthcare facilities (6, 4%). Fifteen patients (10%) required non-invasive ventilation and oxygen support, 3 patients (2%) went on mechanical ventilation. All patients recovered uneventfully, with no mortalities reported. Age was the most significant factor associated with moderate and severe disease. We found no correlation between bowel disease activity and the severity of COVID-19 course. The rate of serious COVID-19 for the 94 patients who had received biologics was significantly lower than that of 50 patients who were not treated with biologics (13/94 vs 24/50; RR 0.29 [95% CI, 0.161–0.515]; p < 0.0001). On adjusting for age, gender, comorbidities, IBD phenotype and activity, the surprising ameliorating effect associated with biologics was profound and significant (OR, 0.082 [95% CI 0.009-0.621], p =0.013) in all age categories. Conclusion: Our results are reassuring and encouraging, and do not suggest that therapeutic immune suppression renders IBD patients particularly vulnerable for more severe course of the COVID-19. Adjusted odds for severe COVID-19 course actually decreased significantly in patients treated with biologics. It could be speculated that cytokine inhibition may mitigate progression of the infection to a devastating hyperinflammatory state. Continuing necessary maintenance immune suppression seems to be appropriate and safe approach, despite the COVID-19 pandemic.